(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The harmonious interplay between architecture and nature is a hallmark of historical urban landscapes across civilizations. This study investigates the stylistic approaches used by architects and planners in historical areas to integrate natural elements into the built environment. Emphasis is placed on Central Asian, Islamic, and European contexts. Through a multidisciplinary methodology involving case studies, field observations, spatial analysis, and historical interpretation, the paper identifies core stylistic patterns—such as biomimicry in ornamentation, climate-responsive structures, and landscape-inclusive spatial planning. The results demonstrate that traditional architecture often prioritized environmental compatibility, leading to sustainable forms that responded to both ecological and cultural needs. The findings offer implications for contemporary urban planning and environmental design, suggesting that historical principles can inform future architectural sustainability.